“A Self You Have Not Yet Learned How to Love”: Building Asian/Queer//Queer/Asian Possibilities Through Archival Speculation - Han, Yingying; Wagner, Travis (Archivaria, 2025)
Archives often preserve materials that reinforce privileged identities and marginalize LGBTQIA+, BIPOC, and disabled communities. Furthermore, there is only limited theoretical work addressing how to ethically document intersectional identities, especially the dual embodiments of Asianness and queerness. Inspired by K.J. Rawson’s theorizing of accessing transgender//desiring queer archival logics, we employ critical case studies to analyze how Asian/queer//queer/Asian identities are represented in archival collections. Our study finds that Asian/queer//queer/Asian theory offers a new lens and new tools to combat archival erasure and misrepresentation resulting from heteronormativity, white supremacy, and cisgender misogyny. This article develops three critical case studies focusing on the white queer gaze toward Asian queer bodies in archives, the disidentification of Asian/queer//queer/Asian identities within archival records, and the use of archival speculation to explore Asian/queer//queer/Asian identities. This work makes both practical and theoretical contributions. Practically, we advocate for proactive archival practices that better represent such identities, avoiding essentialist representations. We also highlight the importance of embodied knowledge and the positionality of scholars and practitioners whose lived experiences centre Asian queer identities along with approaches like revisiting collections, creating reparative descriptions, and reading against the archival grain. Theoretically, we argue for archival speculation as a legitimate mode of inquiry and a process of knowledge production, positioning archives as sites that encourage disidentification.